Altered Experienced Thermoregulation in Depression—No Evidence for an Effect of Early Life Stress - von Salis, Sarina; Ehlert, Ulrike; Fischer, Susanne (Frontiers in Psychiatry, 2021)
Objectives Accumulating evidence suggests that individuals with depression are characterised by difficulties in thermoregulatory cooling. The aim of this study was to investigate, for the first time, whether depressed individuals are aware of these alterations, what their physical consequences are and whether they may be rooted in early life stress. Methods A total of N=672 healthy individuals from the general population were recruited to participate in an online survey. Participants were divided into depressed vs. non-depressed using the Patient Health Questionnaire. Experienced autonomic and behavioural thermoregulation as well as vigilance problems in response to temperature increases were assessed by the Experienced Temperature Sensitivity and Regulation Survey. The Childhood Trauma Questionnaire was administered to assess early life stress. Results Controlling for age, sex, body mass index, and physical activity, depressed vs. non-depressed did not differ in their experienced autonomic responses to temperature increases. However, they reported greater difficulties in concentrating and drowsiness/fatigue in warm environments (p=.029), during physical exertion (p=.029), and during stress (p<.001). There were no differences in the experienced thermoregulation between depressed individuals with vs. without early life stress. Conclusions Depressed individuals experienced more severe physical impairments (i.e., greater vigilance problems) in response to warmth when compared to non-depressed individuals. These differences were not attributable to comorbid illnesses, the intake of medication, or physical deconditioning. Further enquiries in clinical populations are warranted to investigate to what extent the observed alterations map onto specific symptoms of depression (e.g., sleep disturbances).